The Gilded Age - Shrock, Joel (American popular culture through history., 2004)
The Gilded Age--the time between Reconstruction and the Spanish-American War--marked the beginnings of modern America. The advertising industry became an important part of selling the American Dream. Americans dined out more than ever before, and began to take leisure activities more seriously. Women's fashion gradually grew less restrictive, and architecture experienced an American Renaissance. Twelve narrative chapters chronicle how American culture changed and grew near the end of the 20th century. Included are chapter bibliographies, a timeline, a cost comparison, and a suggested reading lis.